Small-Scale Universality and Large-Scale Diversity: Comment on “Drivers of Structural Features in Gene Regulatory Networks: From Biophysical Constraints to Biological Function” by O.C. Martin, a. Krzywicki, and M. Zagorski - Ispolatov, y (Elsevier B.V., 2016)
Sin Resumen Disponible